Genetic Characterization of Resistance to Pyrenophora teres f. teres in the International Barley Differential Canadian Lake Shore - Dinglasan, Eric; Hickey, Lee; Ziems, Laura; Fowler, Ryan; Anisimova, Anna; Baranova, Olga; Lashina, Nina; Afanasenko, Olga (Frontiers in Plant Science, 2019)
Genetic resistance to net form of net blotch (NFNB) in the international barley differential Canadian Lake Shore (CLS) was characterized and mapped. A doubled haploid (DH) population generated from a cross between CLS and susceptible cultivar Harrington was evaluated at the seedling stage using eight diverse Pyrenophora teres f. teres (Ptt) isolates and at the adult stage in the field using natural inoculum. To effectively map the CLS resistance, comparative marker frequency analysis (MFA) was performed using 8,762 polymorphic DArT-seq markers, where ‘resistant’ and ‘susceptible’ groups each comprised 40 DH lines displaying the most extreme phenotypes. Five DArTseq markers were consistently detected in eight disease assays, which was designated qPttCLS and deemed to harbor the locus underpinning CLS resistance. Four of these markers were present onto the barley DArTseq physical map and spans a region between 398203862 – 435526243 bp which were found to consist several genes involved in important plant functions such as disease response and signaling pathways. While MFA only detected the 3H region, genetic analyses based on segregation patterns were inconsistent, suggesting complex inheritance or variation in phenotypic expression of qPttCLS, particularly in the field. This study represents progress towards connecting Ptt pathotype surveys with the corresponding resistance genes in barley differentials. The markers associated with qPttCLS are useful for marker-assisted selection in breeding programs.